The proposed death penalty towards baby dumping offenders: is it a solution? / Maghfirah Mohd Yunus, Mohd Zakey Ramlee and Siti Nurfarahin Mohd Zaki - Mohd Yunus, Maghfirah; Ramlee, Mohd Zakey; Mohd Zaki, Siti Nurfarahin (Universiti Teknologi MARA, Sarawak, 2011)
This research has been conducted by the three part five students of Diploma in Public Administration under the Faculty of Administrative Science and Policy Studies. Under the supervision of our supervisor, Miss Noni Harianti Binti Junaidi, and our lecturer who teaches us this course (PAD 340), Mr Leftenan Colonel Saiful Anwar, we are given the authorities to complete this research with full of commitment and quality.